2023
DOI: 10.3390/diagnostics13132142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Scoliosis Severity Based on Posturographic X-ray Images Using a Contrastive Language–Image Pretraining Model

Artur Fabijan,
Robert Fabijan,
Agnieszka Zawadzka-Fabijan
et al.

Abstract: Assessing severe scoliosis requires the analysis of posturographic X-ray images. One way to analyse these images may involve the use of open-source artificial intelligence models (OSAIMs), such as the contrastive language–image pretraining (CLIP) system, which was designed to combine images with text. This study aims to determine whether the CLIP model can recognise visible severe scoliosis in posturographic X-ray images. This study used 23 posturographic images of patients diagnosed with severe scoliosis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…CLIP is designed to process and understand both text and images simultaneously, allowing it to perform tasks such as image classification, object detection, and image generation. Fabijan et al [26] used 23 postural images of patients with severe scoliosis, evaluated by two neurosurgery experts. The images are fed into the CLIP system and the predictions obtained are compared with the actual data.…”
Section: Early Imaging Screeningmentioning
confidence: 99%
“…CLIP is designed to process and understand both text and images simultaneously, allowing it to perform tasks such as image classification, object detection, and image generation. Fabijan et al [26] used 23 postural images of patients with severe scoliosis, evaluated by two neurosurgery experts. The images are fed into the CLIP system and the predictions obtained are compared with the actual data.…”
Section: Early Imaging Screeningmentioning
confidence: 99%
“…Our previous study sheds light on the capabilities of the publicly accessible contrastive language-image pretraining (CLIP) system in recognizing severe cases of single-curve scoliosis. The results showed that although some AI models possess the ability to partially recognize scoliosis based on visual data, their effectiveness is limited [21]. Consequently, in our article, we delve into the current state of research on the application of AI models in medicine, highlighting that they are rarely considered in the context of scoliosis, despite the potential to offer new, valuable diagnostic perspectives.…”
Section: Introductionmentioning
confidence: 96%
“…In the context of dynamic advancements in language models, our current research aims to extend our understanding of the capabilities of ChatGPT and Microsoft Bing in analyzing posturographic images of patients diagnosed with scoliosis. Expanding on our previous studies, which evaluated the CLIP system's ability to analyze X-ray images of scoliosis [28] and assessed ChatGPT and other AI models in classifying single-curve scoliosis from radiological descriptions [29], our current research delves deeper into the capabilities of ChatGPT and Microsoft Bing for more complex image analysis tasks. Specifically, we selected images depicting severe single-curve scoliosis, which are considered to be relatively simpler for specialists in spinal pathology to assess.…”
Section: Introductionmentioning
confidence: 99%